CONSTRUCTAL DESIGN OF LATENT HEAT STORAGE SYSTEMS (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
—
Keywords: Constructal law; Evolutionary design; Tree shaped; Energy storage; Phase change materials; Dendritic; Melting; Natural convection